Incidence of Sars-CoV-2 infection in newborns in Sergipe from the second half of 2020 to the first half of 2021 (Research, Society and Development, 2022)
Objective: to demonstrate the incidence of Sars-CoV-2 infection in neonates from the second half of 2020 to the end of the first half of 2021 in the state of Sergipe, allowing a comparison in the monthly progression of the number of neonates who presented the detectable result during this period. Methodology: data were collected from the Laboratory Environment Manager of the Central Public Health Laboratory of Sergipe, GAL-LACEN/SE. The samples were analyzed regarding the tests performed, positivity, sex, age group, period of highest incidence and regionality. The methodology implemented in carrying out the tests for the detection of Sars-CoV-2 was the real-time reverse transcription polymerase chain reaction, real-time RT-PCR. Results: of the total of 439 newborns tested: 141 were positive and 298 were negative for the detection of the virus. 71 were male, while 70 were female. The prevalence of the age group is from 0 to 10 days of life. The month of January 2021 had the highest incidence. The Nossa Senhora de Lourdes Maternity, west of Aracaju-SE, had a higher number of positive tests compared to other health units. Conclusion: The discussion presented was duly explained by the subjectivity of the authors in the face of their research, however, it is necessary and encourages new research in the area, which was precisely one of the pre-established objectives of the authors.